Acute Retroviral Syndrome Is Associated With High Viral Burden, CD4 Depletion, and Immune Activation in Systemic and Tissue Compartments. (7th December 2017) - Crowell, Trevor A; Colby, Donn J; Pinyakorn, Suteeraporn; Fletcher, James L K; Kroon, Eugène; Schuetz, Alexandra; Krebs, Shelly J; Slike, Bonnie M; Leyre, Louise; Chomont, Nicolas; Jagodzinski, Linda L; Sereti, Irini; et al.
Abstract : Acute retroviral syndrome was common during acute HIV infection in Bangkok, Thailand. It was associated with elevated viral loads in blood, colon, and cerebrospinal fluid. Evidence of heightened inflammation persisted after 96 weeks of antiretroviral therapy. Abstract: Background: Many individuals with acute human immunodeficiency virus infection (AHI) experience acute retroviral syndrome (ARS), which is associated with adverse long-term clinical outcomes. Methods: Participants presenting for voluntary human immunodeficiency virus (HIV) testing were enrolled during AHI in Bangkok, Thailand. ARS was defined by ≥3 qualifying signs/symptoms. HIV burden, immunophenotypes, and biomarkers were stratified by ARS diagnosis at enrollment and after up to 96 weeks of antiretroviral therapy (ART). Results: From 212382 samples screened, 430 participants were enrolled during AHI, including 335 (78%) with ARS. Median age was 26 years and 416 (97%) were men. Sixty (14%) underwent sigmoid biopsy and 105 (24%) underwent lumbar puncture during AHI. Common symptoms included fever (93%), fatigue (79%), pharyngitis (67%), and headache (64%). Compared to those without ARS, participants with ARS were in later Fiebig stages with higher HIV RNA in blood, colon, and cerebrospinal fluid; higher total HIV DNA in blood; CD4 depletion in blood and colon; and elevated plasma tumor necrosis factor alpha (TNF-α), C-reactive protein, and D-dimer (all P < .05). Subgroup analyses of Fiebig I/II participants (95 with ARS, 69 without) demonstrated similar findings. After 96 weeks of ART, TNF-α and interleukin 6 were elevated in the ARS group ( P < .05) but other biomarkers equilibrated. Conclusions: ARS was associated with high viral burden, CD4 depletion, and immune activation across multiple body compartments during AHI and prior to ART. Persistent inflammation despite suppressive ART could contribute to increased morbidity in individuals who experience ARS.